TFG: a novel regulator of ULK1-dependent autophagy. (4th July 2021) - Cecconi, Francesco; Nazio, Francesca
ABSTRACT: TRK-fused gene (TFG) is a protein implicated in multiple neurodegenerative diseases and oncogenesis. We have recently shown that, under starvation conditions, TFG contributes to spatial control of autophagy by facilitating Unc-51 like autophagy activating kinase 1 (ULK1)-microtubule-associated protein 1 light chain 3 gamma (MAP1LC3C) interaction to modulate omegasome and autophagosome formation. Defective TFG-mediated autophagy could thus be postulated as a possible contributor to ontogenesis or progression of TFG-related diseases.